2020
DOI: 10.1002/ehf2.12680
|View full text |Cite
|
Sign up to set email alerts
|

Multimarker approach including CRP, sST2 and GDF‐15 for prognostic stratification in stable heart failure

Abstract: Aims Inflammation and cardiac remodelling are common and synergistic pathways in heart failure (HF). Emerging biomarkers such as soluble suppression of tumorigenicity 2 (sST2) and growth differentiation factor-15 (GDF-15), which are linked to inflammation and fibrosis process, have been proposed as prognosis factors. However, their potential additive values remain poorly investigated. Methods and results Here, we aimed at evaluating inflammatory and remodelling biomarkers to predict both short-term and long-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
2
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 44 publications
2
24
2
4
Order By: Relevance
“…It shows promise as a biomarker following STelevation acute myocardial infarction, predicting both short-and long-term outcomes (6). Another recent study by Kuster et al demonstrated that GDF-15 is useful in predicting middle term events in stable heart failure (7). One previous study by Heringlake et al could demonstrate that preoperatively raised levels of GDF-15 were an independent predictor of outcome following cardiac bypass surgery (9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It shows promise as a biomarker following STelevation acute myocardial infarction, predicting both short-and long-term outcomes (6). Another recent study by Kuster et al demonstrated that GDF-15 is useful in predicting middle term events in stable heart failure (7). One previous study by Heringlake et al could demonstrate that preoperatively raised levels of GDF-15 were an independent predictor of outcome following cardiac bypass surgery (9).…”
Section: Discussionmentioning
confidence: 99%
“…A novel approach of improving these models could be the inclusion of biomarkers for pre-interventional risk strati cation. The use of established and emerging biomarkers, such as CRP and GDF-15, has shown signi cant promise as predictors of outcome in myocardial infarction and heart failure (6,7). Additionally, the measurement of biomarkers would be a reliable variable, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…(11) Ultimately, a high level of sST2 in blood plasma leads to myocardial fibrosis and dysfunction of the ventricles of the heart. (15) The main sources of sST2 are cardiac fibroblasts and cardiomyocytes in response to stress or injury. Recent studies have demonstrated soluble ST2 to be a strong predictor of cardiovascular outcomes in both chronic and acute heart failure.…”
Section: Introductionmentioning
confidence: 99%
“…(16) The weaknesses of the NT-proBNP diagnostic capabilities, namely that its representativeness depends on some comorbid conditions of patients (impaired renal function, anemia, COPD, obesity), encourages scientists to search for a more stable diagnostic marker for patients with a different EF of CHF. Despite the fact that separate studies have already been conducted (7,15,17) to assess the relationship of sST2 with other characteristics of CHF patients with different LVEF, the results obtained are contradictory.…”
Section: Introductionmentioning
confidence: 99%
“…sST2 was identified as a new prognostic biomarker in HF, independent from age, kidney function, anemia or BMI [ 6 , 8 ]. Recently, our team demonstrated that another biomarker GDF-15 added substantial information on patients’ prognosis [ 9 ]. Urokinase-type plasminogen activator receptor (UPAR) is a glycoprotein involved in tissue reorganization events and regulation of plasminogen [ 10 , 11 ].…”
mentioning
confidence: 99%